1995
DOI: 10.1002/aja.1002030406
|View full text |Cite
|
Sign up to set email alerts
|

Number of adrenergic and Islet‐1 immunoreactive cells is increased in avian trunk neural crest cultures in the presence of human recombinant osteogenic protein‐1

Abstract: OP-1, also known as BMP-7, is a member of the TGF-P superfamily of proteins and was originally identified on the basis of its ability to induce new bone formation in vivo. OP-1 mRNA is found in the developing kidney and adrenal gland as well as in some brain regions (Ozkaynak et al. [1991] Biochem. Biophys. Res. Commun. 179116123). We have tested the effect of recombinant human OP-1 on quail trunk neural crest cultures. The number of catecholamine-positive cells which developed after 7 days in vitro in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 79 publications
1
58
1
Order By: Relevance
“…For instance, BMP-4 and BMP-7 are expressed in the dorsal aorta and direct sympathetic neuronal differentiation into the adrenergic characteristics [80]. BmP-4 and BMP-7 induce a tyrosine hydroxylase (TH)-immunoreactive adrenergic phenotype in cultures of avian neural crest cells [81,82]. We also found that BMP-4 and BMP-7 induce catecholamine production in the presence of mineralocorticoid in adrenal medullar cells.…”
Section: Bmp-4 and -7 Ameliorate Glomerular Mesangial Cell Proliferatmentioning
confidence: 86%
“…For instance, BMP-4 and BMP-7 are expressed in the dorsal aorta and direct sympathetic neuronal differentiation into the adrenergic characteristics [80]. BmP-4 and BMP-7 induce a tyrosine hydroxylase (TH)-immunoreactive adrenergic phenotype in cultures of avian neural crest cells [81,82]. We also found that BMP-4 and BMP-7 induce catecholamine production in the presence of mineralocorticoid in adrenal medullar cells.…”
Section: Bmp-4 and -7 Ameliorate Glomerular Mesangial Cell Proliferatmentioning
confidence: 86%
“…Noggin-treatment also affected the development of the eye, whereas control embryos, receiving control CHO cells, had normal sized eyes and the ciliary ganglion was present. To investigate whether the effects on ciliary neurons are an indirect result of the missing (Varley et al, 1995;Reissmann et al, 1996;Shah et al, 1996;Schneider et al, 1999) and parasympathetic ciliary neurons (the present study). The differential expression of the BMP-downstream transcription factor dHand suggests that sympathetic and ciliary neuron precursors display differences that determine BMP downstream signaling and in turn neuron identity (illustrated by the different shading of sympathetic and parasympathetic precursor cells).…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic neuron generation is initiated by signals from the midline structures when neural crest precursor cells aggregate to form sympathetic ganglion primordia. Major components of these signals are BMP family members, which are essential and sufficient to induce the generation of sympathetic neurons from neural crest cells in vitro and in vivo (Varley et al, 1995;Reissmann et al, 1996;Shah et al, 1996;Shah and Anderson, 1997;Schneider et al, 1999). BMP2/4 and 7 are produced by the dorsal aorta before and during sympathetic neuron development (Reissmann et al, 1996;Shah et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of avian adrenergic differentiation by TGF-b and related proteins has been described by Howard and Gershon (1993;TGF-b1), Varley et al (1995;osteogenic protein-1) and Varley and Maxwell (1966;BMP-2 and BMP-4). Our data are in agreement with these reports and extend them by the additional observation of enhanced expression of a sensory neuron marker.…”
Section: Neurogenesismentioning
confidence: 99%